The Relationship Between Knowlendge and Attitudes of Mothers of Toddlers to Posyandu Visit at Posyandu Sentosa 1 Labuhan Dalam - Suwarniati, Gusti Ayu; Evrianasari, Nita; Isnaini, Nurul (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background : In Indonesia, D/S coverage in 2020 is 61.3%, in Lampung province in 2021 it is 72.8% (Indonesian Ministry of Health, 2021). The coverage of toddlers who are weighed (D / S) in Bandar Lampung City is 66.55% while the coverage of toddlers who are weighed and up (N / D) in 2021 Lampung province is 91% with the city of Bandar Lampung as much as 93% (Lampung Provincial Health Office, 2021).Preliminary study data conducted at the posyandu in the port village recorded a D / S target of 88% in 2022. Objective: to determine the relationship between knowledge and attitudes of mothers of toddlers to the Sentosa 1 Labuhan Dalam posyandu visit. Methods: Observational analytic research design and cross sectional approach. The research was conducted at Posyandu Sentosa I, Labuhan Dalam village in February-July 2023. The population is all mothers of toddlers who are in Posyandu Sentosa 1 Labuhan Dalam during 2022 with a total of 80 respondents. The research instrument used a questionnaire. Data analysis with univariate analysis, namely with distribution tables and bivariate analysis using the Chi Square test.Results: the relationship between knowledge and maternal activeness with a p value of 0.006 (p 0.05) and the relationship between the attitude of mothers of toddlers with a p value of 0.008 (p 0.05). Conclusion: there is a relationship between knowledge and the activeness of mothers in visiting the posyandu and the relationship between the attitude of mothers of toddlers in visiting the posyandu.Suggestion: as a reference in further / similar research and can be an input or description to conduct an evaluation in improving posyandu activities.Keywords: Knowledge, Attitude, Posyandu Visits, Mother of Toddlers